NORMATIVE AND LEGAL FRAMEWORK FOR SOCIAL SUPPORT OF YOUTH IN UZBEKISTAN (Scientific journal of the Fergana State University, 2025)
In Uzbekistan, the regulatory and legal framework for supporting young people and addressing various socio-economic and political tasks is actively evolving. This process involves developing comprehensive policies and legislation aimed at ensuring the well-being, education, and active participation of young people in society. Therefore, this article examines the adoption of significant legal documents that define the main concepts of youth policy formation in Uzbekistan and the foundations of youth support. These documents serve as the basis for the research and implementation of youth policy, providing a scientific foundation for further development and application in this field.